2020
DOI: 10.7717/peerj.8992
|View full text |Cite
|
Sign up to set email alerts
|

Full-length transcriptome and targeted metabolome analyses provide insights into defense mechanisms of Malus sieversii against Agrilus mali

Abstract: Malus sieversii is the wild progenitor for many cultivars of domesticated apple and an important germplasm resource for breeding. However, this valuable species faces a significant threat in the areas north of the Tianshan Mountains in China, by the invasion of Agrilus mali, a destructive pest of apple trees belonging to the family Buprestidae. Our preliminary study has has shown that there may be resistance to this insect in M. sieversii plants in the field, but the corresponding molecular mechanisms remain u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…These results aligned with previous studies indicating that plants can activate the phenylpropanoid biosynthesis and flavonoid biosynthesis pathways in response to pathogen infection. This resulted in the production of various compounds such as phenolics, flavonoids, lignin, and anthocyanin pigments ( Chen et al., 2019 ; 2020; Mei et al., 2020 ; Sudheeran et al., 2021 ). However, the specific alterations in genes and metabolites in the phenylpropanoid biosynthesis and flavonoid biosynthesis pathways in different age groups of P. notoginseng under RKN infection remain unclear, and further investigation is required to identify the key genes and metabolites associated with the defense against RKN damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results aligned with previous studies indicating that plants can activate the phenylpropanoid biosynthesis and flavonoid biosynthesis pathways in response to pathogen infection. This resulted in the production of various compounds such as phenolics, flavonoids, lignin, and anthocyanin pigments ( Chen et al., 2019 ; 2020; Mei et al., 2020 ; Sudheeran et al., 2021 ). However, the specific alterations in genes and metabolites in the phenylpropanoid biosynthesis and flavonoid biosynthesis pathways in different age groups of P. notoginseng under RKN infection remain unclear, and further investigation is required to identify the key genes and metabolites associated with the defense against RKN damage.…”
Section: Discussionmentioning
confidence: 99%
“…The usability of the RNA-Seq data and the results of the differential expression analysis were validated through the application of quantitative real-time reverse-transcription PCR (qRT-PCR) technology ( Mei et al., 2020 ; Xin et al., 2021 ). Twelve disease-resistant-related DEGs from the phenylpropanoid biosynthesis pathway were specifically selected for qRT-PCR verification.…”
Section: Methodsmentioning
confidence: 99%
“…For further metabolomics analysis of secondary metabolites, 2-year-old C. paliurus seedlings of resistant (Wufeng) and susceptible (Jinggangshan) cultivars were inoculated following the IPI method as described earlier. The sample preparation, extract analysis, metabolite separation, and detection were conducted by MetWare Biological Science and Technology (Wuhan, China) following their standard procedures, which were previously described by Li et al (2021) and Mei et al (2020) . In brief, 100 mg crushed, freeze-dried sample was extracted overnight at 4°C with 0.6 mL 70% (v/v) aqueous methanol.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from lignin, several intermediate compounds during lignin biosynthesis also possess the pest resistance capacity. For examples, the resistant cotton varieties presented high content of ferulic acid, which significantly delayed the larval weight gain and increased the mortality of cotton bollworm (Helicoverpa armigera) (Mao et al, 2007), moreover, targeted metabolome analysis showed higher elevation of trans-cinnamic acid, caffeine and ferulic acid after the Malus sieversii resistant strains were infested by Agrilus mali (Mei et al, 2020).…”
Section: Introductionmentioning
confidence: 99%